Ecological agricultural network - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
An extensive consultation process between NGOs, farmers groups and scientists is currently under way to develop an International Ecological Agriculture Network (IEAN). Ongoing discussions point to the urgent need to give more support to the great...